2016
DOI: 10.1007/s11482-016-9483-6
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Consumption and well-Being among Older Adults: Does Age or Life Situation Matter?

Abstract: This study investigated the associations between leisure consumption and well-being in older adults (50-74 years old). To find out whether these associations are age-specific, they were compared with the associations observed among younger adults (18-49 years old). Differences between the older adults by age and life situation were also examined. This study was based on the "Finland 2014 -Consumption and Life style" survey (N=1351), conducted among a representative sample of the Finnish adult population. Well-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Leisure activities, especially the so called structured or serious ones such as arts and crafts, volunteering, sports, hobbies, attending cultural events, and reading (Stebbins, 2007 ), are important predictors of both hedonic and eudaimonic well-being (Delle Fave and Bassi, 2003 ; Lee et al, 2014 ; Kuykendall et al, 2015 ). These activities provide individuals with opportunities for engaging in autonomously chosen tasks, consistent with the person's interests and self-determined goals, and for experiencing positive emotions, competence enhancement and mastery, as well as social integration and connectedness (Sotgiu et al, 2011 ; Bassi and Delle Fave, 2013 ; Toepoel, 2013 ; Kekäläinen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Leisure activities, especially the so called structured or serious ones such as arts and crafts, volunteering, sports, hobbies, attending cultural events, and reading (Stebbins, 2007 ), are important predictors of both hedonic and eudaimonic well-being (Delle Fave and Bassi, 2003 ; Lee et al, 2014 ; Kuykendall et al, 2015 ). These activities provide individuals with opportunities for engaging in autonomously chosen tasks, consistent with the person's interests and self-determined goals, and for experiencing positive emotions, competence enhancement and mastery, as well as social integration and connectedness (Sotgiu et al, 2011 ; Bassi and Delle Fave, 2013 ; Toepoel, 2013 ; Kekäläinen et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…(2015) found that the association between leisure and subjective well‐being was significant for active leisure activities but not for passive leisure. Similarly, a study on Finnish elderly found that only travel had a positive influence on both the mental and physical domains of well‐being; other activities like exercise affected only physical well‐being (Kekäläinen et al., 2017). As found in our study, the literature has suggested that it is not just having leisure experiences, but the content and quality of the leisure that matters to satisfaction outcomes in later life (Carstensen et al., 1999; DeLeire & Kalil, 2010; Headey et al., 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Street usage promoting psychological satisfaction for older adults (Source: Authors). leisure, consumption of health products and living materials (Kekäläinen et al, 2016;Boehm et al, 2018). Few studies have investigated the reemployment of older adults, an important focus because it can increase older adults' psychological satisfaction through the embodiment of their social value.…”
Section: Figurementioning
confidence: 99%